(untitled) (Plant Tissue Culture and Biotechnology, 2009)
The first and preliminary genetic linkage map of the jute genome was constructed with RAPD markers using two parents (variety O-9897 and accession no. 1805) and their F2 populations. Linkage analysis at a LOD (Log of odds base 10) score of 3.0 and a maximum distance 50 cM revealed 18 linkage groups. Among the 18 linkage groups, 15 contained single locus and the remaining three groups 16, 17 and 18 contained 2, 11 and 12 loci, respectively. The three multi locus linkage groups varying in length from 15.9 - 241.7 cM, snapped a total length of 463.7 cM with an average marker density of 19.6 cM between adjacent markers. The basic chromosome number of Corchorus spp. is seven (2n = 14), so in saturated map, seven linkage groups should have been obtained to represent the genome. But for linkage group analysis, the effort was very limited and the total number of loci (40) was also low. Key words: Jute, Linkage map, RAPD, Polymorphism D.O.I 10.3329/ptcb.v18i2.3647 Plant Tissue Cult. & Biotech. 18(2): 165-172, 2008 (December)